Pelaksanaan Tugas Pokok Pengawas dalam Pelayanan Bimbingan dan Konseling Sekolah Menengah Tingkat Atas (Studi di Kota Pariaman Sumatera Barat) - Matondang, Anas Monandar; Prayitno, Prayitno; Jaya, Yahya (Universitas Negeri Padang, 2016)
This research is motivated because supervision of Guidance and Counseling (GC) in the senior high school was not optimum. The purpose of this study was to reveal and describe the implementation of the basic tasks related to monitoring, assessment, and coaching by GC Supervisor to GC Teacher or Counselor. This study used quantitative approach with descriptive methods. The samples in this research were 33 people GC Teacher or Counselor at senior high school level in city of Pariaman with total sampling technique. The instrument used is Likert scale models. Finding of this study are as follows: (1) the quality of the implementation of monitoring by the Supervisor GC into GC Teacher or Counselor in senior high school are in the enough category, and the vocational high school are in the enough category,(2 the quality of the implementation of the assessment by GC Supervisor into GC Teacher or Counselor in senior high school are in the enough category, and the vocational high school are in the enough category, (3) and implementation guidance for GC Teacher or Counselor by GC supervisor in senior high school are in the enough category, while the vocational high school also in good category. Monitoring, assessment, and guidance that carried by GC Supervisor for GC Teacher or Counselor still needs to be improved and developed in order to advance the implementation of services GC in senior high school. The implication of this study can be used as a reference and material for consideration on the implementation of the basic tasks of GC Supervisor in senior high school.